A Simulation Model for a Hybrid-Electric Craft in Restricted Waters - Francesco Mauro; Ubaldo la Monaca; Alberto Marinò; Vittorio Bucci (Journal of Advanced Transportation)
Sustainable mobility is one of the most challenging issues for passenger transport inside environmental protected areas and ecologically fragile environments. To reduce the pollutant emissions, the adoption of electric or hybrid-electric solutions for crafts propulsion is a suitable option for green navigation. However, the operation in restricted basin leads also to specific critical issues for the vessel sailing, as dealing with shallow or restricted waters and transit under low air-gap bridges. The combination of these constraints with the adoption of a hybrid-electric propulsion system increases the design difficulties also for a small craft, requiring the use of advanced simulation models to assess the vessel performances. This work presents a simulation model for a small passenger craft that will operate in the Grado Lagoon. The model combines the hydrodynamic issues of manoeuvring and propulsion in restricted water with the simulation of the electric loads and capacity of the energy storage system installed onboard. The simulations performed with the developed simulation system are in accordance with data measured during trials on a prototype of the vessel. The developed model is a powerful tool for designers in order to rapidly assess the green capabilities of new projects since the early design stages.